The Reconstruction of Proto-Malayo-Javanic - Nothofer, B. (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 1975)
The work is concerned with the reconstruction of the phonemes of Proto-Malayo-Javanic, the last proto-language which is directly continued by the Sundanese, Javanese, Malay, and Madurese.